Cut to the bone : a thriller - Caan, Alex, 1983- (New York : Skyhorse Publishing, 2016)
"For fans of the TV show The Fall, this debut thriller is a fresh spin on a classic police procedural that explores the psychological implications of a life lived online. Ruby Day is a young vlogger, a rising star of YouTube, and a wholesome role-model to millions of teenage girls. And she is missing. Detective Inspector Kate Riley, the head of a new high-powered team of detectives, and Detective Superintendent Zain Harris, the newest member of the team and a poster boy for multiracial policing, are brought in for what they expect to be a routine runaway. Then a video of a wild-eyed Ruby running through the woods and begging for her life is posted online. Amid mounting hysteria and heightened media coverage calling for Ruby's safe return, Riley and Harris must decode the dark secrets of this seemingly squeaky-clean internet darling. Their hunt leads them to a smug ex-boyfriend who hungers for online fame of his own, a culture of online cyber bullying by anonymous thugs, and a corporation of ruthless advertisers who exploit online celebrities for their network of eager consumers. It becomes increasingly clear that the case is more complicated and nightmarish than Riley and Harris could have imagined. And the videos keep coming. This debut novel is a slick, contemporary police procedural that explores the dichotomy of public life and one lived online. For fans of Megan Abbot and Kimberly McCreight, Cut to the Bone provides a harrowing glimpse into the friendships, ambitions, and secrets of the internet generation"--
Includes bibliographical references and index.
Keywords: Murder -- Investigation -- Fiction; Internet -- Fiction; FICTION / Mystery & Detective / Police Procedural; FICTION / Technological; FICTION / Suspense; FICTION / Contemporary Women; Mystery fiction; Suspense fiction